PH and temperature dual-response lignin-based amphiphilic polymer and micelle as well as preparation method and application of pH and temperature dual-response lignin-based amphiphilic polymer and micelle
By developing lignin-based amphiphilic polymers and micelles with dual response pH and temperature, combined with silver nanoparticles, the problems of untimely release of existing anti-cancer drugs and multidrug resistance are solved, and the problem of in-definite environments is achieved The effect of targeted release of drugs improves therapeutic efficiency and reduces biological cytotoxicity.
Patent Information
- Application Number
- CN202411141220.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-02-14
AI Technical Summary
Existing anti-cancer drugs are not released in time when targeting tumor cells, resulting in poor treatment effects and may develop multidrug resistance due to bacterial infections. The existing drug delivery system is difficult to solve these problems.
Develop a pH- and temperature-responsive lignin-based amphiphilic polymer and micelle prepared by photoinduced atom transfer radical polymerization reaction (Photo ATRP), combined with silver nanoparticles to achieve targeted drug release in specific environments .
The system can quickly release drugs under the acidic and lower temperature environment of tumor tissue, improve treatment efficiency, while reducing multidrug resistance through antibacterial effects, and reduce biological cytotoxicity due to the use of natural materials.
Smart Images

Figure BDA0005000853370000031 
Figure BDA0005000853370000071 
Figure BDA0005000853370000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical macromolecular polymer materials, and specifically relates to a pH and temperature dual-responsive lignin-based amphiphilic polymer and micelle, and a preparation method and application thereof. Background Art
[0002] The clinical application of traditional anticancer drugs faces shortcomings such as poor water solubility, lack of targeting to tumor cells, and poor tissue permeability, and does not always achieve the expected therapeutic effect. Therefore, how to accurately attack the site of malignant tumor lesions is particularly important. At the same time, the anti-cancer process is often accompanied by bacterial infection. It is reported that bacteria are speculated to be a potential carcinogen. They can put the body in an inflammatory environment to promote the occurrence of tumors. They may also make chemotherapy drugs ineffective and produce multidrug resistance, thereby protecting tumors from treatment. One of the problems facing current drug delivery is that when the drug-loaded micelles reach the target tumor tissue, the drug needs to be released quickly and in a targeted manner to improve the anti-tumor efficacy of pathological cells and avoid drug resistance. Therefore, the development of anticancer and antibacterial drug delivery agents is crucial to improve the efficiency of drug administration in the body and reduce the risk of side effects. At present, there is an urgent need to develop a safe and convenient drug delivery system for the delivery of these natural anticancer drugs.
[0003] In recent years, amphiphilic polymer nano-micelle delivery systems can flexibly load drugs and antibacterial agents, and carry them to overcome physiological and pathological barriers, complete continuous and targeted delivery, and achieve anti-tumor and antibacterial effects, which has become one of the key directions for the research and development of new drug delivery systems. In the field of nano drug delivery, smart polymer micelles with stimulus-sensitive characteristics have been explored to trigger the release of drugs at target sites in response to the appropriate environment of tumor tissue. Among the various stimulus-sensitive anti-tumor drug nanocarriers, there are light-responsive, acid-responsive, reductive environmental-responsive, enzyme-responsive, etc., which are collectively referred to as smart-responsive polymer micelles. In addition, alkali lignin is a natural material with a wide range of sources, has biocompatibility, low toxicity, is cheap and easy to obtain, and due to the unique physical and chemical properties of alkali lignin, its rich hydroxyl and phenolic groups provide potential for simple modification, making it have great potential in the fields of biotechnology and pharmaceuticals. Summary of the invention
[0004] In order to solve the above-mentioned shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a pH and temperature dual-responsive lignin-based amphiphilic polymer.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned pH and temperature dual-responsive lignin-based amphiphilic polymer; the method first uses a brominating agent 2-bromoisobutyryl bromide (BiBB) to brominate the terminal hydroxyl group of alkali lignin (AL) to obtain a macroinitiator (AL-Br), and then uses the macroinitiator to sequentially initiate a temperature-responsive monomer N-isopropylacrylamide (NIPAM), a pH-responsive monomer 2-(dimethylamino)ethyl methacrylate (DMAEMA), and a hydrophilic monomer monomethoxypolyethylene glycol methacrylate (PEGMA) to perform photoinduced atom transfer radical polymerization (Photo ATRP) to obtain a pH and temperature dual-responsive lignin-based amphiphilic polymer (AL-(PNIPAM-PDMAEMA-PPEGMA) 2 .
[0006] Another object of the present invention is to provide a pH and temperature dual-responsive lignin-based amphiphilic polymer micelle; the micelle is obtained by dissolving, dialyzing and lyophilizing the pH and temperature dual-responsive lignin-based amphiphilic polymer.
[0007] Another object of the present invention is to provide the application of the above-mentioned pH and temperature dual-responsive lignin-based amphiphilic polymer and polymer micelles; the polymer and its micelles have both anti-tumor and antibacterial effects, and can be used to prepare drugs with both anti-tumor and antibacterial effects.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A pH and temperature dual-responsive lignin-based amphiphilic polymer having a structure shown in the following formula (1):
[0010]
[0011] Among them, x=4, y=37, z=37.
[0012] The number average molecular weight of the polymer is 46.8 Kda.
[0013] The above-mentioned method for preparing a pH and temperature dual-responsive lignin-based amphiphilic polymer comprises the following steps:
[0014] (1) dissolving alkali lignin in sodium hydroxide solution, stirring and centrifuging to remove insoluble matter; then dropping hydrochloric acid into the supernatant to adjust the pH to 6, centrifuging and taking the supernatant to continue to drop hydrochloric acid to adjust the pH to 4, centrifuging again and taking the lower layer of suspension, filtering, washing with water, and freeze-drying to obtain purified alkali lignin;
[0015] (2) Weighing purified alkali lignin into a reaction container, evacuating and nitrogen-filling the reaction container three times, and then successively adding N,N-dimethylformamide and anhydrous triethylamine to the reaction container, and then adding 2-bromoisobutyryl bromide under ice bath conditions, and stirring at room temperature for 24 hours; after the reaction is completed, pouring the obtained solution into excess deionized water for washing, and then centrifuging and freeze-drying to finally obtain the macromolecular initiator AL-Br;
[0016] (3) The macromolecular initiator AL-Br and the temperature-responsive monomer N-isopropylacrylamide (NIPAM) obtained in step (2) are fully dissolved in a solvent N,N-dimethylformamide (DMF), and then the catalyst Cu Br 2 Aqueous solution, ligand tris(2-dimethylaminoethyl)(Me 6 TREN), reducing agent disodium ethylenediaminetetraacetate (Na 2 EDTA), halogenating agent sodium bromide (NaBr), and graphene quantum dots (GQDs) were added in sequence and stirred for 5 minutes to make them evenly mixed; after heating reaction, pH-responsive monomer 2-(dimethylamino)ethyl methacrylate (DMAEMA) and hydrophilic monomer monomethoxypolyethylene glycol methacrylate (PEGMA) were added in sequence to carry out polymerization reaction, and after the reaction, the catalyst was removed to obtain pH and temperature dual-responsive lignin-based amphiphilic polymer AL-(PNIPAM-PDMAEMA-PPEGMA) 2 .
[0017] The macromolecular initiator AL-Br, CuBr in step (3) 2 , temperature-responsive monomer N-isopropylacrylamide, pH-responsive monomer 2-(dimethylamino)ethyl methacrylate, hydrophilic monomer monomethoxypolyethylene glycol methacrylate, tris(2-dimethylaminoethyl), graphene quantum dots, disodium ethylenediaminetetraacetate, and sodium bromide have a molar ratio of 1:0.03:60:60:100:4.7:0.005:0.13:0.13.
[0018] The heating reaction described in step (3) refers to heating to 30-60°C.
[0019] The reactions described in step (3) are all carried out under 460nm blue light and sealed conditions.
[0020] A pH and temperature dual-responsive lignin-based amphiphilic polymer micelle is obtained by dissolving the pH and temperature dual-responsive lignin-based amphiphilic polymer in DMF, and performing dialysis and freeze-drying.
[0021] The application of the pH and temperature dual-responsive lignin-based amphiphilic polymer in the preparation of drugs having both anti-tumor and antibacterial effects.
[0022] The application of the pH and temperature dual-responsive lignin-based amphiphilic polymer micelles in the preparation of drugs with both anti-tumor and antibacterial effects.
[0023] The drug is prepared according to the following steps:
[0024] (1) A solution of pH- and temperature-responsive lignin-based amphiphilic polymer micelles was mixed with AgNO 3 The solutions were mixed to obtain a mixed solution, which was stirred in the dark at room temperature for 48 h to obtain a brown-yellow reaction solution; AL-(PNIPAM-PDMAEMA-PPEGMA) was obtained by dialysis and freeze-drying. 2 @Ag micelles; the amount of the pH and temperature dual-responsive lignin-based amphiphilic polymer micelles is based on the raw material pH response monomer 2-(dimethylamino)ethyl methacrylate, and AgNO 3 The molar ratio is (9-3):1;
[0025] (2) Camptothecin (CPT) and the above-obtained AL-(PNIPAM-PDMAEMA-PPEGMA) 2 The Ag micelles were dissolved in DMF and stirred for 2 h to obtain camptothecin solution and silver-loaded polymer solution; the camptothecin solution and the silver-loaded polymer solution were then mixed and stirred for 6 h, followed by dialysis and freeze-drying to obtain lignin silver-loaded micelle drug AL-(PNIPAM-PDMAEMA-PPEGMA) 2 @Ag@CPT.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] (1) The lignin micelles obtained in the present invention are composed of GQDs as photocatalysts and less than 500 ppm of catalyst CuBr 2 The dual catalytic system is formed together through a blue light induced atom transfer radical polymerization (Photo ATRP) reaction; this system reduces the amount of copper used and reduces biological cell toxicity.
[0028] (2) The lignin micelles obtained by the present invention have significant pH responsiveness, which enables the drug to be released at the target site in the appropriate environment of the tumor tissue, thereby greatly improving the problem of targeted drug delivery.
[0029] (3) The lignin micelles obtained by the present invention can overcome the multi-drug resistance existing in the current clinical treatment of tumors: by simultaneously encapsulating silver nanoparticles and anticancer drugs, the combined anti-tumor and antibacterial purposes can be achieved.
[0030] (4) Alkali lignin is a natural material with a wide range of sources, good biocompatibility and low toxicity. In addition, since alkali lignin has rich hydroxyl and phenolic groups and unique physical and chemical properties, it provides potential for modification. The modified alkali lignin has great potential in the fields of biotechnology and pharmaceuticals. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 AL-(PNIPAM-PDMAEMA-PPEGMA) in Example 1 2 H NMR spectrum.
[0032] Figure 2 AL-(PNIPAM-PDMAEMA-PPEGMA) in Example 1 2 GPC curve of .
[0033] Figure 3 AL-(PNIPAM-PDMAEMA-PPEGMA) in Experimental Example 1 2 Dual response detection curve.
[0034] Figure 4 AL-(PNIPAM-PDMAEMA-PPEGMA) in Experimental Example 2 2 @UV and XRD detection curves of Ag.
[0035] Figure 5 AL-(PNIPAM-PDMAEMA-PPEGMA) in Experimental Example 3 2 In vitro release curve of @Ag@CPT.
[0036] Figure 6 AL-(PNIPAM-PDMAEMA-PPEGMA) in Experimental Example 4 2 Cell proliferation inhibition curve of @Ag@CPT.
[0037] Figure 7 AL-(PNIPAM-PDMAEMA-PPEGMA) in Experimental Example 5 2 In vitro antibacterial activity curve of @Ag@CPT. DETAILED DESCRIPTION
[0038] The present invention is further described below with reference to specific embodiments, but they should not be construed as limiting the present invention.
[0039] Example 1: Preparation of lignin micelles AL-(PNIPAM-PDMAEMA-PPEGMA) 2 (x=4, y=37, z=37)
[0040] (1) Purification of alkali lignin: Take a 500 mL dry beaker equipped with a stirrer, weigh the unpurified alkali lignin (AL, 8 g, 40 mmol) and dissolve it in a sodium hydroxide solution (NaOH, 200 mL, 2 M), transfer it to a magnetic stirrer and stir it thoroughly for 10 min. Then, hydrochloric acid (HCl, 2 M) was added dropwise to the solution until the pH value was adjusted to 6, the solution was centrifuged and the supernatant was taken, and hydrochloric acid (HCl, 2 M) was continued to be added dropwise to it until the pH value was adjusted to 4. After centrifugation again, the suspension was taken, washed with water and filtered three times, and freeze-dried for 48 hours to obtain a dark brown powder solid (purified alkali lignin).
[0041] (2) Preparation of macroinitiator AL-Br: A 250 mL dry three-necked flask was equipped with a stirrer, and the purified alkali lignin (AL, 1.56 g, 0.7 mmol) obtained in step (1) was weighed and added to the reaction flask, which was sealed with a reverse rubber stopper and subjected to three vacuum-nitrogen ventilation cycles. N, N-dimethylformamide (DMF, 106.5 mL) was then injected into the flask, and anhydrous triethylamine (TEA, 3.94 mL) was then injected therein. The reaction solution was cooled to 0°C with an ice-water bath, and 2-bromoisobutyryl bromide (BiBB, 3.52 mL) was slowly added dropwise under ice-bath conditions, and stirred at room temperature for 24 hours. After the reaction was completed, the resulting solution was poured into 1 L of deionized water, repeatedly washed and centrifuged three times, and freeze-dried for 48 hours to obtain a brown powder solid (AL-Br). The synthetic reaction formula of this step is shown in formula (1).
[0042]
[0043] (3) Preparation of lignin polymer AL-(PNIPAM-PDMAEMA-PPEGMA) 2 : Add the macroinitiator AL-Br (47.5 μmol) obtained in step (2), the first monomer N-isopropylacrylamide (NIPAM, 2.85 mmol), and 3 mL of DMF to a 10 mL single-necked flask and fully dissolve them. 2 Aqueous solution (0.02M, 1.4μmol), Me 6 TREN (223 μmol), Na 2 EDTA (6.34 μmol), NaBr (6.34 μmol), and GQDs (1 mg / mL, 250 μL) were added in sequence and stirred thoroughly for 5 min.
[0044] min to mix evenly. The whole reaction was carried out under 460nm blue light, and the fully stirred reaction solution was heated to 60℃ for reaction for a period of time. After 9h, the temperature was lowered to 50℃ and the second monomer 2-(dimethylamino)ethyl methacrylate (DMAEMA, 4.75mmol) was added to continue the reaction. After 15h, the temperature was lowered to 30℃ and the third monomer monomethoxypolyethylene glycol methacrylate (PEGMA, 4.75mmol) was added to continue the reaction for 12h. After the reaction, DMF was added to the reaction solution and stirred to dissolve it. The catalyst was removed by filtration through a neutral alumina column (DMF was used as an eluent). The obtained reaction solution was concentrated by rotary evaporation and slowly added to ten times the amount of cold n-hexane for precipitation. The solution was dissolved and precipitated again, and the reaction was repeated three times. Finally, it was dried under vacuum at 80℃ for 1 day to obtain the pH and temperature dual-responsive lignin-based amphiphilic polymer AL-(PNIPAM-PD MAEMA-PPEGMA) 2 The synthesis reaction formula of this step is shown in formula (2). The molecular structure and composition were analyzed by NMR and GPC. The results are shown in Figure 1 and Figure 2 , M n =46.8KDa, M w / M n =1.07.
[0045]
[0046] (4) Preparation of lignin micelles AL-(PNIPAM-PDMAEMA-PPEGMA) 2 : Polymer micelles were prepared by dialysis. 100 mg of the pH and temperature dual-responsive lignin-based amphiphilic polymer AL-(PNIPAM-PDMAEMA-PPEGMA) obtained in step (3) was added to 2 Dissolved in 25 mL DMF, transferred to a dialysis bag with a molecular weight cutoff of 3.5 kDa, and dialyzed in 1 L of deionized water for 48 h. During the dialysis process, the water was changed every 2 h in the first 12 h, and then every 6 h. After filtering through a 0.45 μm filter, lignin micelles were obtained by freeze drying, namely pH and temperature dual-responsive lignin-based amphiphilic polymer micelles (AL-(PNIPAM-PDMAEMA-PPEGMA) 2 micelles).
[0047] Example 2: Preparation of lignin silver-loaded micelles AL-(PNIPAM-PDMAEMA-PPEGMA) 2 @Ag.
[0048] Preparation of lignin loaded silver micelles AL-(PNIPAM-PDMAEMA-PPEGMA) 2@Ag: Silver-loaded polymer micelles were prepared by dialysis. 3 The solutions were mixed to obtain [DM AEMA]:[AgNO 3 ] in a molar ratio of 9:1, 6:1 and 3:1. 3 Taking the molar ratio of ] as 6:1 as an example, 7 mL of the pH and temperature dual-responsive lignin-based amphiphilic polymer micelles (AL-(PNIPAM-PDMAEMA-PPEGMA) obtained in Example 1 was first added. 2 micelles) solution (2 mg / mL, where [DMAEMA] = 2.2*10 -1 mmol) and 3 mL of deionized water were mixed evenly in a 50 mL reaction bottle, and then 1 mL of AgNO was slowly added dropwise to the reaction bottle. 3 Solution ([AgNO 3 ]=0.37*10 -1 mmol), stirred in the dark at room temperature for 48 hours to obtain a brown-yellow reaction solution, and then the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 3.5 kDa and dialyzed in 1L deionized water for 48 hours. During the dialysis process, the water was changed every 2 hours for the first 12 hours, and then every 6 hours. After filtration with a pore size of 0.45um, lignin silver-loaded micelles were obtained by freeze drying, namely AL-(PNIPAM-PDMAEMA-PPEGMA) 2 The silver micelles were prepared by the same method as above.
[0049] Example 3: Preparation of lignin-loaded silver-loaded drug-loaded micelles AL-(PNIPAM-PDMAEMA-PPEGMA) 2 @Ag@CPT.
[0050] Preparation of lignin-loaded silver-loaded drug micelles AL-(PNIPAM-PDMAEMA-PPEGMA) 2 @Ag@CPT: First, camptothecin CPT (0.3-1 mg) and AL-(PNIPAM-PDMAEM A-PPEGMA) obtained in Example 2 were mixed. 2 @Ag micelles (2 mg) were dissolved in 0.4 mL DMF and stirred for 2 h to obtain camptothecin solution and silver-loaded polymer solution; the camptothecin solution and silver-loaded polymer solution were then mixed and stirred for 6 h, and then transferred into a dialysis bag with a molecular weight cutoff of 3.5 kDa and dialyzed in 1 L deionized water for 48 h; the water was changed every 2 h for the first 12 h during the dialysis process, and then changed every 6 h; then filtered through a pore size of 0.45 μm and freeze-dried to obtain lignin silver-loaded micelles AL-(PNIPAM-PDMAEMA-PPEGMA)2 @Ag@CPT.
[0051] Experimental Example 1: AL-(PNIPAM-PDMAEMA-PPEGMA) 2 Temperature and pH response assay
[0052] Each sample was prepared in an ultrapure aqueous solution at a concentration of 2 mg / mL, and the relationship between transmittance and temperature was measured by a variable temperature UV-visible spectrophotometer at a wavelength of 500 nm. 2 The micelle solution was placed in a series of test tubes. Different amounts of hydrochloric acid (HCl, 0.1 M) solution were dropped into each test tube to make the pH values 3, 4, 5, 6, 7.4, 8, and 9, respectively. After sufficient stirring and ultrasonication, the DLS particle size of the solution in each test tube was tested and recorded.
[0053] Figure 3 AL-(PNIPAM-PDMAEMA-PPEGMA) prepared in the present invention 2 The temperature and pH response performance of micelles. Figure 3 As shown in (A), when the temperature exceeds the LCST (33.1°C), the transmittance of the micelle solution decreases. This is because the hydrophobicity of the micelles increases with the increase in temperature, and the transmittance decreases accordingly. Figure 3 In (B), as the pH gradually decreases, the D h This is because the tertiary amine groups of the side chains of PDMAEMA are continuously protonated, and the hydrophilicity of PDMAEMA is gradually enhanced, resulting in micelle swelling. When the pH drops to less than 4, the PDMAEMA blocks are completely protonated, and the strong electrostatic repulsion between chains causes the micelle structure to slightly dissociate, and D h There was a decline.
[0054] Experimental Example 2: Determination of the particle size and morphology of AgNPs loaded with silver micelles
[0055] Take 3 mL of [DMAEMA]:[AgNO 3 The ultraviolet absorbance of lignin loaded silver micelles with molar ratios of 9:1, 6:1 and 3:1 was measured.
[0056] In order to prove the existence of silver in the prepared nanomaterials, XRD analysis was performed. Figure 4 (B), [DMAEMA]: [AgNO 3In the XRD pattern of lignin silver-loaded micelles with a molar ratio of 6:1, the peaks at 2θ of 38.1°, 44.5°, 64.7° and 77.6° correspond to the lattice planes (111), (200), (220) and (311), respectively, showing the face-centered cubic structural characteristics of metallic silver nanoparticles. This proves that AgNPs are successfully encapsulated in the polymer.
[0057] like Figure 4 As shown in (A), when PDMAEMA / AgNO 3 When the molar ratio increases, the particle size of AgNPs decreases. This is due to the different number of AgNPs formed by the coordination reduction of tertiary amine, which leads to the hypochromic shift of the UV-visible spectrum, and the maximum absorption peaks are located at 420nm, 418nm, and 414nm respectively. 3 ] molar ratio of lignin silver micelles = 3:1, this ratio contains a high amount of Ag, the particle size is larger and it is easier to agglomerate to form large particles, which affects the antibacterial performance, and too high silver content will increase cytotoxicity and cause damage to normal physiological cells; while [DMAEMA]:[AgNO 3 ] molar ratio = 9:1 lignin silver micelles, this ratio contains low Ag content and weak antibacterial effect. Comprehensive consideration selected the middle ratio [DMAEMA]: [AgNO 3 ]The lignin-loaded silver micelles with a molar ratio of 6:1 were used in the subsequent antibacterial experiments.
[0058] Experimental Example 3: In vitro drug release experiment
[0059] 0.15 mg of the silver-loaded drug-loaded lignin micelles obtained in Example 3 were dispersed in 3 mL of phosphate buffer (PBS) and transferred into a dialysis bag (molecular weight cutoff of 3500). The dialysis bag was placed in 100 mL of PBS and placed in a shaker at 37°C and 100 rpm for in vitro release. 3 mL of samples were taken at regular intervals, filtered through a 0.45 μm filter head, and its ultraviolet absorbance at 371 nm was measured, and 3 mL of the corresponding fresh buffer was added. The cumulative release of the drug (CPT) was calculated using the following formula:
[0060]
[0061] Where: E r : Cumulative drug release, %; V e : Buffer replacement volume, 3mL; V 0 : Total volume of buffer, 103 mL; C i : Sample concentration at the i-th replacement sampling, mg / L; m CPT : The mass of CPT in micelles, mg; n: The number of times of replacing buffer.
[0062] like Figure 5 As shown in the figure, in the environment of human body simulated normal tissue (37℃, pH 7.4), the release rate of CPT is relatively slow, the cumulative drug release in 24h does not exceed 25%, and there is no obvious drug burst release. This is because under neutral conditions, the tertiary amine group of the pH-sensitive block DMAEMA is in a deprotonated state, and the core structure of the micelle is compact, which increases the resistance of drug diffusion outward. When the pH is reduced to the environment simulated tumor cell endosomes (37℃, pH 5.0), the pH-responsive group is completely protonated into a hydrophilic block, and due to electrostatic repulsion, the micelle swelling degree increases, and camptothecin is released quickly. The cumulative release amount in 24h and 108h reaches 46% and 83%, respectively. The drug release rate in the 30℃ environment is slightly lower than the release result at 37℃. It shows that the release rate is enhanced near the transition temperature of the PNIPAM polymer. Therefore, the release behavior can be adjusted by changing the ambient temperature / pH value.
[0063] Experimental Example 4: Cytotoxicity Test Experiment
[0064] The lignin micelles obtained in Example 1 and the lignin silver-loaded micelles ([DMAEMA]:[AgNO 3 ] molar ratio = 6:1), the effect of lignin silver-loaded drug-loaded micelles obtained in Example 3 on cell activity. The cells were inoculated on a 96-well plate (1×10 4 pcs / well / 100 μL) at 37°C, 5% CO 2 Culture in a constant temperature incubator for 24 hours. Then add different concentrations of blank micelles, silver-loaded micelles and silver-loaded drug-loaded micelles to the 96-well plate and continue to culture for 48 hours. After the incubation, aspirate the old culture medium in the wells, carefully rinse three times with ice PBS, and then add 100 μL of fresh culture medium to each well. Then add 10 μL of CCK8 solution to each well and continue incubating at 37°C for 2 hours. Finally, use an enzyme reader to measure the optical density (OD) at 450nm. The formula for calculating cell viability is as follows:
[0065]
[0066] The results are as follows Figure 6 As shown, Figure 6 (A) Blank micelles and AL-(PNIPAM-PDMAEMA-PP EGMA) 2 @The cytotoxicity results of Ag micelles showed that when the micelle concentration increased to 800 μg / mL, there was still a cell survival rate of about 75%, indicating that the polymer carrier has low toxicity and will not be toxic to normal tissues within the actual use range. Figure 6 (B) is AL-(PNIPAM-PDMAEMA-PPEGMA) 2Cytotoxicity evaluation results after 48h of co-culture of @Ag@CPT micelles with cells. AL-(PNIPAM-PDMAEMA-PPEGMA) 2 The cytotoxicity of @Ag@CPT increased with the increase of CPT concentration, and the cell killing rate increased significantly. At high concentration (150 μg / mL), more than 65% of the cells were killed by AL-(PNIPA M-PDMAEMA-PPEGMA) 2 @Ag@CPT was killed after co-culture, confirming that the AL-(PNIPAM-PDMAEMA-PPEGMA) obtained in the present invention 2 @Ag@CPT micelles are a promising chemotherapy platform.
[0067] Experimental Example 5: In vitro antibacterial activity test
[0068] Take 200 μL of the solution with a density of about 10 6 CFU / mL of Staphylococcus aureus and Escherichia coli suspensions cultured overnight were added to a 48-well plate, and then 200 μL of different concentrations (0 μg / mL, 100 μg / mL, 200 μg / mL, 400 μg / mL, 600 μg / mL, 800 μg / mL) of lignin micelles of Example 1, lignin silver micelles of Example 2 ([DMAEMA]:[AgNO 3 ] molar ratio = 6:1), and the PBS solution of lignin silver-loaded drug-loaded micelles in Example 3 was added to each well. The cells were cultured in a constant temperature shaker at 37°C and 80 rpm. After 48 h of culture, the optical density (OD) of each group was measured using an enzyme marker. 600 )value.
[0069] like Figure 7 As shown in the figure, the bacterial growth curve is highly correlated with the AgNPs concentration in the LB medium. As the AgNPs concentration increases, the antibacterial effect becomes more significant. Compared with the blank micelles with an antibacterial rate of only about 20%, AL-(PNIPAM-PDMAEMA-PPEGMA) 2 @Ag micelles and AL-(PNIPAM-PDMAEMA-PPEGMA) 2 @Ag@CPT micelles completely inhibited the growth of Staphylococcus aureus and Escherichia coli at concentrations of 600μg / mL and 800μg / mL, respectively (the inhibition rate was as high as 93%). In addition, in the micelle concentration range of 0-800μg / ml, AL-(PNIPAM-PDMAEMA-PPEGMA) 2 @Ag@CPT micelles compared to AL-(PNIPAM-PDMAEMA-PPEGMA) 2The inhibition rates of Escherichia coli and Staphylococcus aureus in the @Ag micelles were ∼20% and ∼15% higher, respectively, indicating that AL-(PNIPAM-PD MAEMA-PPEGMA) 2 @Ag@CPT micelles have significant antibacterial effects on Staphylococcus aureus and Escherichia coli, and are expected to have a good antibacterial effect on the problem of multidrug resistance in anti-tumor diseases.
[0070] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A pH and temperature dual-responsive lignin-based amphiphilic polymer, characterized in that: The polymer has a structure as shown in the following formula (1): Among them, x=4, y=37, z=37.
2. The pH and temperature dual-responsive lignin-based amphiphilic polymer according to claim 1, characterized in that: The number average molecular weight of the polymer is 46.8 Kda.
3. The method for preparing a pH and temperature dual-responsive lignin-based amphiphilic polymer according to claim 1, characterized in that The steps include: (1) dissolving alkali lignin in sodium hydroxide solution, stirring and centrifuging to remove insoluble matter; then dropping hydrochloric acid into the supernatant to adjust the pH to 6, centrifuging and taking the supernatant to continue to drop hydrochloric acid to adjust the pH to 4, centrifuging again and taking the lower layer of suspension, filtering, washing with water, and freeze-drying to obtain purified alkali lignin; (2) Weighing purified alkali lignin into a reaction container, evacuating and nitrogen-filling the reaction container three times, and then successively adding N,N-dimethylformamide and anhydrous triethylamine to the reaction container, and then adding 2-bromoisobutyryl bromide under ice bath conditions, and stirring at room temperature for 24 hours; after the reaction is completed, pouring the obtained solution into excess deionized water for washing, and then centrifuging and freeze-drying to finally obtain the macromolecular initiator AL-Br; (3) The macromolecular initiator AL-Br obtained in step (2) and the temperature-responsive monomer N-isopropylacrylamide are fully dissolved in the solvent N,N-dimethylformamide, and then the catalyst CuBr2 aqueous solution, the ligand tris(2-dimethylaminoethyl), the reducing agent disodium ethylenediaminetetraacetate, the halogenating agent sodium bromide, and the graphene quantum dots are added in sequence, and stirred for 5 minutes to mix them evenly; after heating reaction, the pH-responsive monomer 2-(dimethylamino)ethyl methacrylate and the hydrophilic monomer monomethoxypolyethylene glycol methacrylate are added in sequence to carry out polymerization reaction, and after the reaction, the catalyst is removed to obtain the pH and temperature dual-responsive lignin-based amphiphilic polymer AL-(PNIPAM-PDMAEMA-PPEGMA)2.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the macromolecular initiator AL-Br, CuBr2, temperature-responsive monomer N-isopropylacrylamide, pH-responsive monomer 2-(dimethylamino)ethyl methacrylate, hydrophilic monomer monomethoxypolyethylene glycol methacrylate, tris(2-dimethylaminoethyl), graphene quantum dots, disodium ethylenediaminetetraacetate, and sodium bromide in step (3) is 1:0.03:60:60:100:4.7:0.005:0.13:0.
13.
5. The preparation method according to claim 3, characterized in that: The heating reaction described in step (3) refers to heating to 30-60°C.
6. The preparation method according to claim 3, characterized in that: The reactions described in step (3) are all carried out under 460nm blue light and sealed conditions.
7. A pH and temperature dual-responsive lignin-based amphiphilic polymer micelle, characterized in that: The micelle is obtained by dissolving the pH and temperature dual-responsive lignin-based amphiphilic polymer described in claim 1 in DMF, and then dialyzing and freeze-drying.
8. Use of the pH and temperature dual-responsive lignin-based amphiphilic polymer according to claim 1 or the pH and temperature dual-responsive lignin-based amphiphilic polymer micelle according to claim 7 in the preparation of a drug having both anti-tumor and antibacterial effects.
9. The use according to claim 8, characterized in that: The drug is prepared according to the following steps: (1) A solution of pH and temperature dual-responsive lignin-based amphiphilic polymer micelles is mixed with a AgNO3 solution to obtain a mixed solution, and the mixture is stirred in the dark for 48 hours at room temperature to obtain a brown-yellow reaction solution; AL-(PNIPAM-PDMAEMA-PPEGMA)2@Ag micelles are obtained by dialysis and freeze-drying; the amount of the pH and temperature dual-responsive lignin-based amphiphilic polymer micelles is based on the pH responsive monomer 2-(dimethylamino)ethyl methacrylate as the raw material for its preparation, and the molar ratio of the mixture to AgNO3 is (9-3):1; (2) Camptothecin (CPT) and the above-obtained AL-(PNIPAM-PDMAEMA-PPEGMA)2@Ag micelles were dissolved in DMF and stirred for 2 h to obtain a camptothecin solution and a silver-loaded polymer solution; the camptothecin solution and the silver-loaded polymer solution were then mixed and stirred for 6 h, followed by dialysis and freeze-drying to obtain lignin silver-loaded micelle drug AL-(PNIPAM-PDMAEMA-PPEGMA)2@Ag@CPT.
Citation Information
Cited By
Application of water-soluble miscellaneous [3] aromatic hydrocarbon material as stabilizer in preparation of silver nanoparticles
CN121624441A
Use of a water-soluble hetero[3]arene material as a stabilizer in the preparation of silver nanoparticles
CN121624441B